1999
DOI: 10.1029/1998ja900180
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric conductivity modulation in ULF pulsations

Abstract: Abstract. Using incoherent scatter radar and magnetometer measurements, we report that during terrestrial magnetic Pc5 pulsations in the afternoon sector, a modulation of particle precipitation and ionospheric conductivities by a factor of 2 occurs in addition to high-amplitude variations of electric and magnetic fields. The event thus seems to be considerably more complicated than previously studied ones where information about conductivities was mostly not available. Our groundbased data set gives us several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 32 publications
0
32
1
Order By: Relevance
“…Previously, Buchert et al [1999] found similar differences between the power spectra of magnetometer data and electric field and conductivity measurements made with the EISCAT incoherent scatter radar. They suggested that these differences were due to the magnetometer being influenced by ionospheric currents flowing over a large area (of the order of a few hundred kilometers square), while the EISCAT radar measurements were taken from a much smaller ionospheric area (of the order of a few kilometmers square).…”
Section: Relationship Between Radar and Magnetometer Spectramentioning
confidence: 74%
See 4 more Smart Citations
“…Previously, Buchert et al [1999] found similar differences between the power spectra of magnetometer data and electric field and conductivity measurements made with the EISCAT incoherent scatter radar. They suggested that these differences were due to the magnetometer being influenced by ionospheric currents flowing over a large area (of the order of a few hundred kilometers square), while the EISCAT radar measurements were taken from a much smaller ionospheric area (of the order of a few kilometmers square).…”
Section: Relationship Between Radar and Magnetometer Spectramentioning
confidence: 74%
“…[10] Besides the Buchert et al [1999] case study, we know of only two other studies that have measured the ionospheric electric field spectrum (see Table 1). Furthermore, we have found no other estimates in the literature of the power spectral exponent of the ionospheric electric field or E Â B velocity measured directly with radar in this frequency range (though similar work has been carried out using SuperDARN radar to look at the power spectrum of gravity waves, e.g., Bristow and Greenwald [1997]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations